Natural variability and anthropogenic change in equatorial Pacific surface ocean pCO2 and pH. Issue 2 (26th February 2014) - Sutton, Adrienne J.; Feely, Richard A.; Sabine, Christopher L.; McPhaden, Michael J.; Takahashi, Taro; Chavez, Francisco P.; Friederich, Gernot E.; Mathis, Jeremy T.
Abstract The equatorial Pacific is a dynamic region that plays an important role in the global carbon cycle. This region is the largest oceanic source of carbon dioxide (CO2) to the atmosphere, which varies interannually dependent on the El Niño‐Southern Oscillation (ENSO) and other climatic and oceanic drivers. We present high‐resolution observations of surface ocean CO2 partial pressure (pCO2) at four fixed locations in the Niño 3.4 area with data sets encompassing 10 ENSO warm and cold events from 1997 to 2011. The mooring observations confirm that ENSO controls much of the interannual variability in surface seawater pCO2 with values ranging from 315 to 578 µatm. The mooring time series also capture the temporal variability necessary to make the first estimates of long‐term pH trends in the equatorial Pacific, which suggests that the combination of ocean acidification and decadal variability creates conditions for high rates of pH change since the beginning of the mooring record. Anthropogenic CO2 increases play a dominant role in significant observed seawater pCO2 trends of +2.3 to +3.3 µatm yr−1 and pH trends of −0.0018 to −0.0026 yr−1 across the full time series in this region. However, increased upwelling driven by increased trade winds, a shallower thermocline, and increased frequency of La Niña events also contribute an average of 40% of the observed trends since 1998. These trends are higher than previous estimates based on underway observations and suggest that the equatorial Pacific is contributing a greater amount of CO2 to the atmospheric CO2 inventory over the last decade.